Long-Term Survival of Resected Advanced Gastric Cancer with Hepatic and Pancreatic Invasion - Domen, Hiromitsu (S. Karger AG, 2011)
A 64-year-old man was transferred to our division with a suspicion of gastric cancer. Computed tomography showed widespread irregular thickening of the stomach walls close to the liver and pancreas. Gastrointestinal fiberscopy showed a type 5 tumor in the upper to lower stomach, histologically diagnosed as tubular adenocarcinoma. Gastric cancer with hepatic and pancreatic invasion was diagnosed. Distant metastasis was not proven and complete resection was planned. At laparotomy, the tumor showed general expanding growth and invasion through the lateral segment of the liver and pancreas. Total gastrectomy and combined resection of the distal pancreas, spleen and left segment of the liver were performed. Hepatic and pancreatic invasion and lymph node metastasis were microscopically proven. Pancreatic fistula occurred postoperatively. On postoperative days 40, he was discharged. He received two cycles of adjuvant tegafur/gimeracil/oteracil chemotherapy. He has had no sign of recurrence for 7 years and 8 months.